Korelasi Kompetensi Pedagogik dan Percaya Diri Guru Terhadap Keberhasilan Program SMK Pusat Keunggulan - Joni Firdaus; Sarmini Sarmini; Julia Safitri (Universitas Kristen Satya Wacana, 2023)
SMK Multistudi High School Batam is one of 895 SMKs in Indonesia selected by the government in 2021 to implement the SMK Center of Excellence program. This program hopes to help teachers solve every learning problem to prepare graduates ready to compete in the world of work. This quantitative study uses a sample of 45 teachers at SMK Multistudi High School Batam. This study aims to analyze the correlation between pedagogic competence and teacher confidence in the success of the SMK Center of Excellence program. The result of the study shows that there is a positive and significant correlation between pedagogical competence and the success of the Center for Excellence Vovatiobal High School program, with the result of the t-test showing t count 5.379 >ttable 1.679 ans sig.0.000< α 0.05. It turns out that teacher self-confidence is not correlated with the success of the Center for Excellence Vocational High School program, where the t-score shows a t-score of 0.097 < t-table of 1.679 and sig.0.454 > α 0.05. The study's results show a partially positive and significant correlation between pedagogical competence and teacher confidence in the success of the Center of Excellence in Vocational High School program, with the F test results showing a significance value of less than 0.05 (0.000<0.05).